2022
DOI: 10.1021/acs.analchem.2c01744
|View full text |Cite
|
Sign up to set email alerts
|

Versatile DIY Route for Incorporation of a Wide Range of Electrode Materials into Rotating Ring Disk Electrodes

Abstract: Rotating ring disk electrodes (RRDEs) are a powerful and versatile tool for mechanistically investigating electrochemical reactions at electrode surfaces, particularly in the area of electroanalysis and catalysis. Despite their importance, only limited electrode materials (typically glassy carbon, platinum, and gold) and combinations thereof are available commercially. In this work, we present a method employing three-dimensional (3D) printing in conjunction with machined brass components to produce housing, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Effectively, our method dramatically simplifies the estimation and comparative analysis of • OH by replacing the need for ESR measurements in exchange for a swift, inexpensive electrochemical collection approach. Indeed, although we decided to use SECM because of its steady-state and imaging capabilities, short time scale for species detection, and previous experience in our laboratory with methods for ROS detection, there is no reason why the presented methodology cannot be deployed using other techniques such as the rotating ring-disk electrode (RRDE), provided a suitable disk electrode is available . Many laboratories in countries with limited resources may not have ESR instrumentation available, but it is common to find well-established electrochemical facilities elsewhere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effectively, our method dramatically simplifies the estimation and comparative analysis of • OH by replacing the need for ESR measurements in exchange for a swift, inexpensive electrochemical collection approach. Indeed, although we decided to use SECM because of its steady-state and imaging capabilities, short time scale for species detection, and previous experience in our laboratory with methods for ROS detection, there is no reason why the presented methodology cannot be deployed using other techniques such as the rotating ring-disk electrode (RRDE), provided a suitable disk electrode is available . Many laboratories in countries with limited resources may not have ESR instrumentation available, but it is common to find well-established electrochemical facilities elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…The computed APR values are referenced to the standard hydrogen electrode (SHE) and subsequently referenced to the silver chloride reference electrode (Ag|AgCl). We applied two commonly used SHE reference potentials of 4.28 V and 4.44 V (IUPAC). In addition to different methods for redox potential prediction, we also employed two different solvation methods to determine the optimum E ° prediction: (1) Polarizable Continuum Model (PCM) using the integral equation formalism variant (IEF-PCM); (2) Solvation Model based on Density (SMD) …”
Section: Methodsmentioning
confidence: 99%
“…The data suggested that quantification of the true concentration of OH · generated from water oxidation via EC-EPR is problematic. The use of different cell geometries, such as flow cells and/or rotating disk electrodes, could be beneficial to minimize fouling events and prevent further oxidation of DMPO-OH · , as the product is swept away from the electrode surface. Further investigations are required.…”
Section: Discussionmentioning
confidence: 99%
“…After laser cutting, the electrodes were acid cleaned in a boiling mixture of concentrated sulfuric acid (H 2 SO 4 , >96%, Merk) and potassium nitrate (KNO 3 , 99.97%, Sigma-Aldrich) using a procedure described elsewhere. 31 After cleaning, a bilayer ohmic metal contact (Ti 10 nm/Au 400 nm) was deposited onto the lapped (nucleation) surface using a Moorfield MiniLab sputter system. After deposition, this contact was annealed at 400 °C in air for 5 h. 31 Thin film BDD was also used in these studies (Condias GmbH, Germany; DIACHEM) consisting of a ∼10 μm thick layer of BDD supported on an 8 mm diameter niobium substrate and was used as received.…”
Section: Bdd Materialsmentioning
confidence: 99%
“…31 After cleaning, a bilayer ohmic metal contact (Ti 10 nm/Au 400 nm) was deposited onto the lapped (nucleation) surface using a Moorfield MiniLab sputter system. After deposition, this contact was annealed at 400 °C in air for 5 h. 31 Thin film BDD was also used in these studies (Condias GmbH, Germany; DIACHEM) consisting of a ∼10 μm thick layer of BDD supported on an 8 mm diameter niobium substrate and was used as received. SEM and WLI of this BDD surface can be found in Figures 1c−e and SI.2, respectively.…”
Section: Bdd Materialsmentioning
confidence: 99%